Enhancing Students’ Scientific Literacy Through ESD-based E-modules on Low Carbon Energy Topic - Wafa Hanifah; Diana Rochintaniawati; Rika Rafikah Agustin (Pedagogia: Jurnal Ilmiah Pendidikan, 2025)
Scientific literacy is a foundational competency for addressing the 21st century challenges, especially in the context of transition to low-carbon energy systems. Sadly, there is very little curriculum coverage of sustainability and energy topica; teachers are mostly unprepared; and there are almost no good-quality local instructional materials. Therefore, this study looks into the effectiveness of an ESD-based e-module on low carbon energy topic in promoting scientific literacy among ninth-grade students in Cimahi, Indonesia. Using a quasi-experimental one-group pretes-posttest design, 28 students took part in learning activities that integrated systems thinking, collaboration, and problem-solving competencies. Scientific literacy was measured using a validated 25-item test covering competencies of explaining phenomena scientifically, scientific inquiry, and scientific data interpretation. Results showed that there was a significant increase in mean scientific literacy scores from pretest (64.75) to posttest (80.57); the moderate average N-gain was 0.45. The highest improvement was found in students' ability to seek, evaluate, and use scientific information in decision-making. The statistical analysis used confirmed that the increases were significant. The results suggest that ESD-based e-modules have the potential to bridge educational gaps by making very complex sustainability concepts simpler and fostering critical scientific competencies.